The drivers of cross-border banking expansion: Evidence from East Africa - Odongo Kodongo; Dinah Natto (Kenya Bankers Association (KBA), 2014)
This paper has investigated the drivers for bank expansion abroad in East Africa. We use a Poisson regression model with number of banks going abroad as our dependent variable and several host-country and source-country explanatory variables. Our results indicate that follow-the-customer motive is a strong drive for bank expansion across East Africa. Similarly, the desire for superior returns and the need to escape intense competition in Kenya has pulled banks into foreign markets. Further, favorable regulatory environment abroad is an important factor influencing the expansion of banks into foreign markets. Surprisingly, our results suggest that economic integration is negatively related with bank expansion. Results are robust to alternative measures of foreign bank expansion and estimation procedures. We also run predictive regressions, which show that the single most important factor informing banks' future decisions to move abroad is domestic bank concentration.
Keywords: 330